EFEKTIVITAS PROGRAM COORPORATE SOCIAL RESPONSIBILITY (CSR) DI PT TIRTA INVESTAMA AQUA SUBANG KECAMATAN CISALAK - Zaenal Hirawan; Sri Dinarwati (Department of Public Administration, Muhammadiyah University of Makassar, 2022)
AbstractThis research is motivated by the inadequate clean and healthy lifestyle of the community, because there is an increase in diarrhea cases based on data in 2020, namely 359 sufferers, while in 2021 as many as 613. Educational and outreach patterns from the government and private parties to the community have less impact, because the level of community participation in the CSR program is still low. In this study, the researcher uses a qualitative approach with the inquiry method, that the case study is an exploration of a bounded system or a case/ various case that from time to time go through in-depth data collection and involve various sources of information rich in a context. The results of the study show that not all communities can understand and participate in CSR programs so that the benefits and success rates are relatively diverse. Many obstacles in the implementation of CSR programs cause the level of satisfaction of the private sector, government and beneficiaries will also be different. In terms of input, this program is very adequate, but in terms of output, especially for the beneficiaries, it has not had such a big impact. On the other hand, the goals of this program have positive things but require time and involvement of parties and consistency in its implementation.AbstrakPenelitian ini dilatar belakangi pola hidup bersih dan sehat dari masyarakat yang kurang memadai, karena ada peningkatan kasus diare berdasarkan data tahun tahun 2020 yaitu 359 penderita, sementara tahun 2021 sebanyak 613. Pola edukasi dan sosialisasi dari pihak pemerintah dan swasta kepada masyarakat kurang berdampak, karena tingkat turut serta masyarakat dalam program CSR masih rendah. Dalam Penelitian ini peneliti menggunakan pendekatan kualitatif dengan metode inquiry, bahwa studi kasus sebuah eksplorasi dari suatu sistem yang terikat atau suatu kasus/beragam kasus yang dari waktu ke waktu melalui pengumpulan data yang mendalam serta melibatkan berbagai sumber informasi yang kaya dalam suatu konteks. Hasil penelitian menunjukan bahwa tidak semua masyarakat dapat memahami dan turut serta dalam program CSR sehingga manfaat, tingkat keberhasilan relatif beragam. Banyak kendala dalam pelaksanaan program CSR menyebabkan tingkat kepuasan dari pihak swasta, pemerintah dan penerima manfaat juga akan berbeda. Dari sisi input, program ini sangat memadai, namun dari segi output khususnya bagi penerima manfaat belum memberikan dampak yang begitu besar. Dari sisi yang lain, tujuan program ini mempunyai hal yang positif namun memerlukan waktu dan keterlibatan pihak dan konsistensi dalam pelaksanaannya.